Performance of some barley genotypes in relation to soil acidity - Ben, José Renato; Peruzzo, Geraldino; Minella, Euclydes (Pesquisa Agropecuaria Brasileira, 2014)
Aiming at assessing the performance of some barley (Hordeum vulgare L.) genotypes in relation to soil acidity, in 1983 an experiment was conducted in pots under greenhouse conditions, using soil of the Passo Fundo Soil Mapping Unit (Dark-Red Dystrophic Latosol). Treatments consisted of five barley genotypes and six correction levels of soil acidity, arranged in a 5 x 6 factorial, with randomized blocks and three replications. Above-ground green and dry matter, height of plants, quantity of tillers and spikes, dry matter and length of roots and, in the soil, the factors representing acidity were determined in plants harvested at flowering time. Results obtained evidenced barley response to acidity neutralization by liming, shown through parameters determined in the plant. Above-ground dry matter showed a high association level with remaining parameters determined in the plant and with soil acidity factors, indicating that barley reaction to these factors can be expressed by the production of above-ground dry matter. Genotypes FM 404, PFC 7802, and Antarctica 1 showed greater tolerance to soil acidity than FM 434 and PFC 8026, being the latter the most sensible genotype.
Keywords: soil acidity; liming; aerial parts of plant; plant dry matter; tillers; heads; plant height; roots; root length; soil aluminum